(untitled) (Research, Society and Development, 2021)
The necessity of controlling the vegetative growth of fruit trees is a growing concern for farmers since vigorous plants tend to have lower fruit yields. The use of chemicals that inhibit the vegetative growth of plants, such as prohexadione-calcium (PCa), an inhibitor of gibberellins which is currently used as a growth regulator for apple trees, is an agricultural practice aimed to help in reducing pruning time and cost. Pear trees grafted on vigorous rootstocks tend to present high rates of vegetative growth, hindering fruit production. Thus, this work aimed to evaluate the effect of the application of different doses of the plant growth regulator PCa on the vegetative growth, pruning time, radiation incidence, and productive and quality parameters of ‘Packham’s Triumph’ and ‘Hosui’ pears grafted on vigorous rootstocks. Two PCa applications were carried out, the first after the falling of petals (2009-10-10), and the second twenty-one days after the first (2009-11-02). The observed results showed a significant effect of PCa in reducing the vegetative growth of the pear trees and the pruning time in both cultivars. The effect on photosynthetic active radiation (PAR) was observed only in the ‘Packham’s Triumph’ variety, not being observed for the ‘Hosui’ pear trees. No statistical difference was observed relative to the quality parameters and yield of the fruits, in both cultivars, showing that PCa application has not caused any deleterious effect on fruit development.